ANALISIS KESULITAN BERBICARA PESERTA DIDIK 5B SDN GALUR 01 JAKARTA DALAM PEMBELAJARAN BAHASA INGGRIS - Melinda Dwi Safitri; Chrisnaji Banindra Yudha; Indah Wardatussa’idah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the speaking difficulties of grade 5B students at SDN Galur 01 Jakarta. Speaking skill is an important part of English learning in Elementary School. This research used a qualitative approach with a descriptive method. Data were collected through  classroom observation , and semi – structured interviews with the teacher and students. The results showed that speaking difficulties are influenced by internal factors such as psychological barriers and lack of habituation in using English, and external factors , namely an unsupportive environment.